2020
DOI: 10.1186/s40352-020-00117-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age and suicidal thoughts and attempted suicide among prisoners

Abstract: Background: Suicide is a major problem across the lifespan, yet rates are highest among middle-aged and older adults; a trend which remains relatively stable across varying sociological settings, including prisons. Despite this understanding, there is limited knowledge on the nature of suicidal thoughts and attempts among older prisoners, especially with respect to how they compare to younger counterparts. The present study aimed to increase insight into the relationship between age and suicidal thoughts and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
4
8
3
Order By: Relevance
“…Our findings are consistent with those of studies reporting that young age is associated with suicidal ideation [38,[57][58][59]. Most mental health problems, including suicidal ideation, occur among people in adolescence and are likely to persist through adulthood if not appropriately resolved [29,60].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with those of studies reporting that young age is associated with suicidal ideation [38,[57][58][59]. Most mental health problems, including suicidal ideation, occur among people in adolescence and are likely to persist through adulthood if not appropriately resolved [29,60].…”
Section: Discussionsupporting
confidence: 91%
“…Race/ethnicity was based on a series of dummy variables: Hispanic, White, Black, and "Other" (i.e., Indigenous, Asian, Hawaiian/ Pacific Islander, or other race/ethnicity). A quantitative measure of age in years (16-84) was used, which was also squared (Age 2 ) to examine the possibility of a curvilinear effect of age on the probability of affirmative response on suicidal outcome measures (this approach is informed by Stoliker et al, 2020). Education is a quantitative measure that captured the highest level of school ever attended prior to the current incarceration (0-18).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…It is worth noting, however, that suicidal outcome measures are linked to individuals' age at the time of the survey and not the exact age(s) at which suicidal events occurred. Given these findings and methodological shortcomings, researchers should further investigate agebased variation in repeat-versus single-suicidal behavior (separately for men and women)with particular focus on factors that might explain this variability (see Stoliker et al, 2020). In light of gender-based findings, it is evident that prison administrators will need to consider implementing gender-tailored risk assessment (Marzano et al, 2016) and psychological interventions (Fazel et al, 2016) to adequately address the specific needs of men and women who are incarcerated and at risk of (repetitive) suicidal behavior.…”
Section: Interpretation Of Findings and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this concern, previous studies showed that suicidal ideation is mostly associated with weak social connections and depression resulting from, among other things, missing old connections and social life even after decades of incarceration [ 61 , 62 ]. Even though prison misconduct is inversely related to the offender’s age [ 2 ] and suicidal attempts are less common among older inmates as compared with younger offenders [ 63 ], suicidal ideation is rather currently more common among older prisoners and it is anticipated that suicide among the ageing population will be an increasing problem in the future [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%